The Effects of a Vocabulary Intervention on Teaching Multiple-Meaning Words to Students Who Are d/Deaf and Hard of Hearing. (13th June 2020) - Alqraini, Faisl M; Paul, Peter V
Abstract: Building vocabulary knowledge, especially breadth and depth of word meanings, is a crucial step in assisting students to read and comprehend print independently. A large body of research has documented the low reading achievement levels of a number of Deaf and hard-of-hearing (DHH) students. The goal of the present study was to examine the effects of a vocabulary intervention to teach 24 multiple-meaning words to fourth-grade DHH students in Saudi Arabia by utilizing a single-case experimental design (multiple probe design across participants). A total of 5 students with a profound hearing loss participated in the study. About 3 of 5 received the intervention, whereas two other students served as an additional control component and were administered the pretest and posttest only. The data showed that there was a significant improvement in the recognition and comprehension scores of students who received the intervention. In contrast, students who did not receive the intervention showed no significant improvement on the posttest.